A strange family, or how a new pleolipovirus reveals its friends and relatives. Issue 6 (14th October 2015) - Dyall‐Smith, Mike; Porter, Kate
Summary: A new virus of halophilic A rchaea is reported by Liu et al ., and is remarkable in many ways. SNJ2 is the first temperate, pleomorphic virus (pleolipovirus) that integrates into the genome of its host. Analyses of the virus structure and its genome have provided an unexpected puzzle while at the same time solving another. On the one hand, the study shows a curious relationship exists between SNJ2 and an unrelated provirus (SNJ1) found as a plasmid in the same cell. The presence of SNJ1 appears to allow much higher levels of SNJ2 virus to be produced, although the mechanism involved remains unclear. On the other hand, the curious occurrence of a conserved cluster of pleolipovirus‐related genes found widely distributed among haloarchaeal genomes and known for almost 10 years, now appears to correspond to SNJ2‐related proviruses. Abstract : The genomes of many haloarchaea (extremely halophilic Archaea) contain one or more copies of highly conserved gene clusters that encode capsid‐related proteins similar to those found in pleolipoviruses. Surrounding these gene modules there are usually other virus‐ or plasmid‐related genes but the nature of these odd chromosomal loci has been puzzling. The study by Liu et al. (….) reveals that many (perhaps most) of them are proviruses of a new type of temperate pleolipovirus, as exemplified by SNJ2.